The Possibility for a Greek-Turkish Co-operation before the Balkan Wars - Balogh, Ádám (Études sur la Région Méditerranéenne, 2004)
I would like to demonstrate the possibility of a Greek-Turkish co-operation, namely, when, what concrete ideas appeared between the two nations until the outbreak of the first Balkan War. For this, I deem it necessary to review the meaning of two substantial concepts - "Intermediate Area" and "Graeco-Turkism" - until the Young Turk Revolution.